2019
DOI: 10.7717/peerj.7608
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reverse transcription enzymes and conditions on high throughput amplicon sequencing of the 16S rRNA

Abstract: It is assumed that the sequencing of ribosomes better reflects the active microbial community than the sequencing of the ribosomal RNA encoding genes. Yet, many studies exploring microbial communities in various environments, ranging from the human gut to deep oceans, questioned the validity of this paradigm due to the discrepancies between the DNA and RNA based communities. Here, we focus on an often neglected key step in the analysis, the reverse transcription (RT) reaction. Previous studies showed that RT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…However, previous norovirus HTS studies using custom hexamers reported no improvement in performance compared to random hexamers ( 8 ). While RT aims to produce cDNA that faithfully reflects the starting RNA sample, several studies indicate that the RT reaction can introduce large variability ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous norovirus HTS studies using custom hexamers reported no improvement in performance compared to random hexamers ( 8 ). While RT aims to produce cDNA that faithfully reflects the starting RNA sample, several studies indicate that the RT reaction can introduce large variability ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%